Документальні ресурси загального веб-порталу ЮНЕСКО – міжнародної організації з питань освіти, науки і культури - Кравцова, О. (Архіви України, 2009)
The article is devoted to the UNESCO’s portal documentary resourses, that reflected activities of the Organization portal in the fields of education, science, culture and communication and promoting international co-operation among its Member States and Associate Members. The structure and content of the different resources groups of the UNESCO’s portal are working to create the conditions for the development and sharing of information, communication and knowledge with the universal access to
the documentary information in the fields of UNESCO’activity.